Criminal action of abortion rape health perspective legal and Islamic law - Miftahul Utami (Requisitoire Law Enforcement, 2023)
This study aims to find out the provisions and what abortion as a result of rape is like in 3 aspects, namely Health, Law and Islamic law. The results of the study show that abortion due to rape in terms of health, the law and Islamic law both allow abortion to be carried out due to the health condition of the prospective mother which can be disrupted, such as psychological and physical injuries experienced by the victim. 61 of 2014 Concerning Reproductive Health However, by looking at his condition, that the defendant was a child victim of rape and made considerations in the Law on the Legality of Rape Abortion, then in Decision No. 5/PID.SusAnak/2018/Pn MBN the defendant was found guilty. However, by looking at the conditions that the defendant is a child victim of rape and made considerations for the Law on the legality of rape abortion, then in Decision No. 6/Pid.Sus-Children/2018/Pt and enact Law No. 36 of 2009 concerning Health, PP no. 61 of 2014 concerning Reproductive Health and the MUI Fatwa as the basis for the law on the legality of rape abortion, it is hoped that it can be enforced in the fairest way possible for rape victims who have abortions as relief for the losses that have been experienced by rape women. However, abortion also cannot be done carelessly because the right of the fetus to live is protected by Article 23 of 2009 concerning Child Protection. Cases of abortion rape have occurred in Indonesia, one of which is a 15-year-old boy who was charged with having an abortion as a result of rape by his older sibling.